Analisis Keuangan Publik Islam Dan Keuangan Sosial Islam Terhadap Kesejahteraan Masyarakat Perspektif Ekonomi Islam Studi Kualitatif Pada Pengelolaan Ziswaf - Naufal Prakoso; Fauziyah Fauziyah; Lenny Apriani; Dinda Adelia; Sofi Nur Azizah (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study examines the role of Islamic public finance and Islamic social finance in improving the welfare of Indonesian society from the perspective of Islamic economics. The research background is based on the urgency of optimizing Sharia-based fiscal and social instruments as solutions to poverty and economic inequality, which remain significant challenges in Indonesia. The research aims to analyze the contribution of zakat, infaq, sadaqah, and waqf (ZISWAF), as well as Islamic public finance instruments such as Sharia-based state budgets, toward community welfare indicators. The method employed is descriptive qualitative with a case study approach in Indonesia, reviewing secondary data from BAZNAS reports, the Ministry of Finance, and the Indonesian Waqf Board from 2018 to 2023. The results indicate that transparent and accountable management of Islamic public finance can reduce absolute poverty rates, while optimization of Islamic social finance through productive waqf and program-based zakat has been proven to improve the human development index in various regions of Indonesia. The integration of both instruments within the Islamic economic system contributes significantly to equitable income distribution and the achievement of maqashid al-shariah.